A rapid assessment framework for food system shocks: Lessons learned from COVID-19 in the Indo-Pacific region. Issue 117 (March 2021) - Butler, James R.A.; Davila, Federico; Alders, Robyn; Bourke, R. Michael; Crimp, Steve; McCarthy, John; McWilliam, Andrew; Palo, Anton S.M.; Robins, Lisa; Webb, Michael J.; van Wensveen, Monica; Sanderson, Todd; et al.
Highlights: Few tools exist to guide rapid responses to food system shocks such as COVID-19. We tested a complex systems analysis across 11 countries in the Indo-Pacific region. Our framework enabled integration and triangulation of diverse knowledge and data. Priority interventions and opportunities for potential transformation were identified. Political, economic and institutional issues should be emphasized in future analyses. Abstract: The frequency and severity of shocks to food systems is accelerating globally, exemplified by the current COVID-19 outbreak. In low- and middle-income countries, the impacts have exacerbated existing food system vulnerabilities and poverty. Governments and donors must respond quickly, but few tools are available that identify interventions to build food system resilience, or emerging opportunities for transformation. In this paper we reflect on the application of a systems-based rapid assessment which we applied across 11 Indo-Pacific countries in May-July 2020. Our approach was shaped by three design parameters: the integration of key informants' perspectives engaged remotely within the countries, applicability to diverse food systems and COVID-19 experiences across the region, and the consideration of food systems as complex systems. For the rapid assessment we adopted an analytical framework proposed by Allen and Prosperi (2016). To include a development lens, we added the analysis of vulnerable groups and their exposure, impacts, recovery potential and resilience, and pro-poor interventions. We concluded that the framework and approach facilitated integration and triangulation of disparate knowledge types and data to identify priority interventions and was sufficiently flexible to be applied across food systems, at both national, sub-national and commodity scales. The step-wise method was simple and enabled structured inquiry and reporting. Although the systems concepts appeared more easily transferrable to key informants in some countries than others, potentially transformational interventions were identified, and also some risks of maladaptation. We present a refined framework that emphasises analysis of political, economic and institutional drivers of exposure and vulnerability, the constraints that they pose for building recovery potential and resilience, and trade-offs amongst winners and losers inherent in proposed interventions.